Design and Applications of Multi-Frequency Holographic Subsurface Radar: Review and Case Histories - Ivashov, Sergey I.; Capineri, Lorenzo; Bechtel, Timothy D.; Razevig, Vladimir V.; Inagaki, Masaharu; Gueorguiev, Nikolay L.; Kizilay, Ahmet (MDPI, 2021)
Holographic subsurface radar (HSR) is not currently in widespread usage. This is due to a historical perspective in the ground-penetrating radar (GPR) community that the high attenuation of electromagnetic waves in most media of interest and the inability to apply time-varying gain to the continuous-wave (CW) HSR signal preclude sufficient effective penetration depth. While it is true that the fundamental physics of HSR, with its use of a CW signal, does not allow amplification of later (i.e., deeper) arrivals in lossy media (as is possible with impulse subsurface radar (ISR)), HSR has distinct advantages. The most important of these is the ability to do shallow subsurface imaging with a resolution that is not possible with ISR. In addition, the design of an HSR system is simpler than for ISR due to the relatively low-tech transmitting and receiving antennae. This paper provides a review of the main principles of HSR through an optical analogy and describes possible algorithms for radar hologram reconstruction. We also present a review of the history of development of systems and applications of the RASCAN type, which is possibly the only commercially available holographic subsurface radar. Among the subsurface imaging and remote sensing applications considered are humanitarian demining, construction inspection, nondestructive testing of dielectric aerospace materials, surveys of historic architecture and artworks, paleontology, and security screening. Each application is illustrated with relevant data acquired in laboratory and/or field experiments.
Keywords: holographic subsurface radar; ground-penetrating radar; nondestructive testing; cultural heritage objects; land mine detection; security applications; MILLIMETER-WAVE; MICROWAVE; METAL; RECONSTRUCTION; INSULATION; INSPECTION; SYSTEM; FIELD; GPR; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology